Honey from the Lion: Christianity and the Ethics of Nationalism1. Issue 3 (26th June 2014) - Biggar, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> This book comprises a Christian apologia for nationalism in general and for Scottish separatist nationalism in particular. It is only fair that the reader should know that its reviewer is an Anglo-Scottish unionist.